Clinical profiles and prognosis of acute heart failure in adult patients with dystrophinopathies on home mechanical ventilation. (18th May 2017) - Fayssoil, Abdallah; Yaou, Rabah Ben; Ogna, Adam; Leturcq, France; Nardi, Olivier; Clair, Bernard; Wahbi, Karim; Lofaso, Frederic; Laforet, Pascal; Duboc, Denis; Orlikowski, David; Annane, Djillali
Abstract: Aims: Duchenne muscular dystrophy (DMD) is characterized by respiratory and heart involvements. In the context of permanently wheelchair bound and on mechanical ventilation (MV) patients, the clinical presentation of acute heart failure (AHF) syndrome may be atypical. We sought to describe clinical and genetic profiles and to determine prognosis of DMD and Becker muscular dystrophy (BMD) patients on home MV (HMV), hospitalized for AHF. Methods and results: We included genetically proven DMD and BMD patients on HMV admitted for AHF. A total of 13 patients (11 DMD and 2 BMD) fulfilled the inclusion criteria. Median age was 34.0 [interquartile range (IQR) 26.0; 40.0] years. Median pulmonary vital capacity was 9.0% (6.0; 15.0) of predicted value. Long‐term invasive ventilation was performed in 69% of patients. All the 11 DMD patients carried out‐of‐frame DMD gene mutations. At admission, dyspnoea was present in 46%, lipothymia in 23%, and abdominal discomfort in 38.4% of patients. A total of 53.8% of patients showed anasarca. Cardiogenic shock presentation was found in six patients (46%). Ejection fraction was severely altered [median 25% (IQR 20; 30)]. Intra‐hospital mortality rate was 30%, reaching 53.8 % after 1 year. Previous episodes of AHF ≥ 2 were associated with intra‐hospital mortality ( P  = 0.025). In patients with cardiogenic shock, intra‐hospital mortality rate was 66.6%, reaching 83.3% after 1 year. Conclusions: In adult DMD and BMD patients with severe ejection fraction alteration and on HMV, admitted for AHF, right cardiac signs are frequent. The intra‐hospital and 1 year mortality rate was high and was associated with previous episodes of AHF ≥ 2.